Analisis Persekutuan Masyarakat Budaya Adat Lio Dari Aspek Nilai Kekerabatan Desa Detubinga Kecamatan Tanawawo Kabupaten Sikka - Yulius Dea (IAIN Ambon, 2023)
Yulius Dea. Analysis of the Alliance of the Lio Indigenous Cultural Community from the Aspect of Kinship Values in Detubinga Village, Tanawawo District, Sikka Regency. Thesis. Maumere: Social Sciences and Humanities Education. IKIP Muhammadiyah Maumere. Culture is one of the characteristics of Indonesian society. Through culture each person understands and recognizes the culture they have. This is imprinted in the Lio indigenous cultural community. Where the Lio indigenous people are still very strong with their culture and cultural diversity as in the analysis of the Lio traditional cultural alliance examined from the point of view of kinship. In general and in particular the Lio indigenous people still maintain kinship as a very, very meaningful heritage. This is based on the results of research and interviews. Where the author in his research has found that among the indigenous people of Lio they still have a kinship pattern as inherited from their ancestors. In addition, researchers have found that the Lio indigenous people have long built alliances to forge togetherness in living together.Keywors: Lio custom, fellowship and kinship